2019
DOI: 10.26717/bjstr.2019.12.002294
|View full text |Cite
|
Sign up to set email alerts
|

Micro Total Analysis System Application for Biomedicals: A Mini-Review

Abstract: Recently, the microfluidic system is one of the most trending research topics in the world due to its unique characteristics and great advantages. The present mini-review deals with the application of micro total analysis system for the biomedical fields, such as in situ detection, enrichment, imaging, and quantification of biomolecules and cell. The recent progress of the microfluidic system on cancer, tumor, HIV, diabetes, malaria and tuberculosis was displayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In 2001, Burns and Ramshaw firstly reported that the mass transfer of acetic acid from kerosene to aqueous phase was significantly enhanced by using droplet microfluidic device [33]. As of today, there are many types of microfluidic devices, such as continuous microfluidic devices, droplet microfluidic devices, paper microfluidic devices, and digital microfluidic devices have been fabricated and applied for many applications [34,35]. Each of them serves as a unique platform for certain applications.…”
Section: Droplet Microfluidic Devicementioning
confidence: 99%
“…In 2001, Burns and Ramshaw firstly reported that the mass transfer of acetic acid from kerosene to aqueous phase was significantly enhanced by using droplet microfluidic device [33]. As of today, there are many types of microfluidic devices, such as continuous microfluidic devices, droplet microfluidic devices, paper microfluidic devices, and digital microfluidic devices have been fabricated and applied for many applications [34,35]. Each of them serves as a unique platform for certain applications.…”
Section: Droplet Microfluidic Devicementioning
confidence: 99%
“…Organ-on-chips culture the biological cells and investigate their compatibility and metabolism directly which is hardly monitored by another experimental setup. Because of that, it is possible now for a real-time monitoring of biomarker labeling, drug's mechanism of action, clinical pathology, tissue, and organ physiology just within a microscale portable device and without any victim animal [106,107]. In addition to that, the microfluidic probe has been also employed for a single-cell pharmacological analysis which is remarkable [108,109].…”
Section: Where Is the Microfluidics Today?mentioning
confidence: 99%
“…In the biomedical field, a micro total analysis system, known as a "lab on a chip", is proposed to reduce space and energy. Such a system is portable and integrates several processes that are performed in the laboratory to analyze and evaluate the samples and miniaturize them into a single device [16,17]. Furthermore, several successful research results have also been presented in the field of robotics based on miniaturized sensors and activators [18,19].…”
Section: Introductionmentioning
confidence: 99%